PERAN DINAS SOSIAL DAN PEMAKAMAN KOTA PEKANBARU DALAM MENANGANI ANAK TERLANTAR TAHUN 2013 - Chandra Rizal; Raja Muhammad Amin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
63277The role of the state in providing services to the community should be based on the basic values of Pancasila social justice for all Indonesian people, including in reducing social welfare issues. under the Act of 1945 in Article 34 Paragraph 1 mentioned the poor and neglected children who are maintained by the state, with this Government Pekanbaru Pekanbaru City Regional Regulation No. 12 Year 2008 concerning the social order in which the regulation is described in Chapter 1 Article 1 Paragraph 20, which reads "Social Guidance is a series of activities to grow, increasing the willingness and ability to target social skills counseling to enable them to carry out their social function normative", and verse 22 which says "Treatment is a process or way of preventive action, repressive and rehabilitative services to homeless and children in order to humanize back bums or beggars and children who have trouble on the streets ". Based on some of the phenomena that occur in the field, the writer can formulate the research title "The Role of Social Service and Pekanbaru City Cemetery In Tackling Neglected Children in 2013". A fundamental problem in this research is the large number of abandoned children who have not been scouted as many as 2750 inhabitants that the authority of the government in this regard is the role of the Department of Social and Pekanbaru City Cemetery, then there are many factors inhibiting the implementation of coaching and training both internally and externally. Theory (approach) that I use as a tool of analysis in this study is the role of theory, policy and coordination. While the methods used in this study is a qualitative method, which seeks to analyze the role and constraints derived from observations and aim to reinforce and strengthen a theory so as to obtain information about the current situation. Data collection techniques in this research is to use the techniques of observation, interviews and documentation. It can be concluded in this study that the role of the Department of Social and Pekanbaru City Cemetery is not working as it should because in reducing waif there are still some good in the process of empowerment and service that has not been optimized in accordance with Regulation 12 of 2008 on the Social Order. Then there are many factors that hinder the role of the Department of Social and Pekanbaru City Cemetery ie Internally form of budget, human resources and infrastructure. As well as external human resources and infrastructure that it is still lacking. So we need to realize that in an effort mengenteskan social welfareJom FISIP Volume. 2 No. 2 Oktober 2015 2issues need seriousness of Pekanbaru City Government for the realization ofsocial welfare for the city of Pekanbaru.Keywords : Role of Government, Neglected Children , Empowerment , Service